Cardiac-specific overexpression of thioredoxin 1 attenuates mitochondrial and myocardial dysfunction in septic mice. (December 2016) - Sánchez-Villamil, Juana P.; D'Annunzio, Verónica; Finocchietto, Paola; Holod, Silvia; Rebagliati, Inés; Pérez, Hernán; Peralta, Jorge G.; Gelpi, Ricardo J.; Poderoso, Juan J.; Carreras, María C.
Abstract: Sepsis-induced myocardial dysfunction is associated with increased oxidative stress and mitochondrial dysfunction. Current evidence suggests a protective role of thioredoxin-1 (Trx1) in the pathogenesis of cardiovascular diseases. However, it is unknown yet a putative role of Trx1 in sepsis-induced myocardial dysfunction, in which oxidative stress is an underlying cause. Transgenic male mice with Trx1 cardiac-specific overexpression (Trx1-Tg) and its wild-type control (wt) were subjected to cecal ligation and puncture or sham surgery. After 6, 18, and 24 h, cardiac contractility, antioxidant enzymes, protein oxidation, and mitochondrial function were evaluated. Trx1 overexpression improved the average life expectancy (Trx1-Tg: 36, wt: 28 h; p = 0.0204). Sepsis induced a decrease in left ventricular developed pressure in both groups, while the contractile reserve, estimated as the response to β-adrenergic stimulus, was higher in Trx1-Tg in relation to wt, after 6 h of the procedure. Trx1 overexpression attenuated complex I inhibition, protein carbonylation, and loss of membrane potential, and preserved Mn superoxide dismutase activity at 24 h. Ultrastructural alterations in mitochondrial cristae were accompanied by reduced optic atrophy 1 (OPA1) fusion protein, and activation of dynamin-related protein 1 (Drp1) (fission protein) in wt mice at 24 h, suggesting mitochondrial fusion/fission imbalance. PGC-1α gene expression showed a 2.5-fold increase in Trx1-Tg at 24 h, suggesting mitochondrial biogenesis induction. Autophagy, demonstrated by electron microscopy and increased LC3-II/LC3-I ratio, was observed earlier in Trx1-Tg. In conclusion, Trx1 overexpression extends antioxidant protection, attenuates mitochondrial damage, and activates mitochondrial turnover (mitophagy and biogenesis), preserves contractile reserve and prolongs survival during sepsis.